Seroepidemiologi Nipah Virus pada Kalong dan Ternak Babi di Beberapa Wilayah di Indonesia - Sendow, Indrawati; Field, Hume; Adjid, R.M. Abdul; Syafriati, Tatty; Darminto, Darminto; Morrissy, Chris; Daniels, Peter (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTNipah Virus Seroepidemiology in Flying Fox and Pig Husbandry in Several Areasof Indonesia. Nipah is a dangerous zoonotic disease which was carried by flying fox.The disease had been occurred in Malaysia in 1999 and infect pigs and caused humandeath. Indonesia is adjacent country to Malaysia, hence, a serological study had beenconducted on 156 flying fox (P. vampyrus) sera from North Sumatera, West Java, CentralJava and East Java. Besides that, 2740 pig sera was randomly collected in differentprovinces to detect Nipah infection. Both flying fox and pig sera were tested usingELISA test to detect the presence of Nipah antibody. The results indicated that 37 from156 flying fox sera (23.7%) has antibodies against Nipah virus. Infections were occuredin all sampling sites with the prevalence varied from 18% to 33 %. Meanwhile, no pigsera tested (2740) had antibody against Nipah virus. Based on these results it can beconcluded that Nipah virus infections were occurred in flying fox in some parts inIndonesia, but not in pigs. It was suggested that the presence of Nipah virus in Indonesiashould be anticipated. Hence the distribution of its infection in pigs and human must beanticipated. Monitoring of Nipah infection in areas adjacent to Malaysia must be increasedto detect the entering of the disease in Indonesia.Keywords: Nipah, pigs, flying fox, serology